A Note on Two Classical Theorems of the Fourier Transform for Bounded Variation Functions - Mendoza-Torres, Francisco J. (Communications in Mathematics and Applications, 2016)
Employing the Henstock-Kurzweil integral, we make simple proofs of the Riemann-Lebesgue lemma and the Dirichlet-Jordan theorem for functions of bounded variation which vanish at infinity.